Shifting learning strategies and future selves of Arab postgraduate students in Britain: a qualitative inquiry. Issue 3 (27th May 2021) - Hajar, Anas
ABSTRACT: This paper explores Arab postgraduate students' situated experiences and their actual and dynamic use of learning strategies at a UK university. The qualitative data collected from a written narrative and five subsequent rounds of individual semi-structured interviews suggest that most participants initially clung to their 'aschematic' future selves as they articulated relatively distant goals without employing the appropriate learning strategies to get to them. They anticipated achieving native-like proficiency in English and forming meaningful friendships with locals once they were in the host environment. In response to the changes in assessment mode and the practice of some influential actors, however, the participants gradually began to articulate proximal goals until they visualised their ideal self and embraced the appropriate strategies. The findings of the current study underline the significance of introducing pedagogical interventions in all phases of study abroad to avoid student sojourners' maladaptive behaviour, such as the setting of unrealistic or impractical goals, and deepen their language and intercultural learning. Directions for further research are also suggested.